2016
DOI: 10.1097/md.0000000000004212
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cutaneous abdominal ulcerations secondary to diffuse dermal angiomatosis

Abstract: Background:Diffuse dermal angiomatosis (DDA) is a rare, acquired, reactive vascular proliferation, clinically characterized by livedoid erythematous–violaceous plaques, which frequently evolve to ulceration and necrosis. Histopathologically, it is manifested by a diffuse proliferation of endothelial cells within the full thickness of the dermis. DDA has been mainly associated with severe peripheral atherosclerosis.Methods:We report a 63-year-old woman who presented with multiple erythematous–violaceous plaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…After excluding cases with explicit unifocal involvement, involvement of both breasts, or un-reported location, 13 cases were found in the literature of DDA with multifocal involvement (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), as in our case (Table SI 1 ). Among them, 84.6% involved women, with mean age 58 years; 46.2% involved current smokers; and 46.2% featured atherosclerosis, as expected according to the review of Touloei et al (3) The thigh was the most common location, observed in 61.5% of cases.…”
Section: Multifocal Diffuse Dermal Angiomatosis: a Reflection Of High Cardiovascular Riskmentioning
confidence: 85%
See 2 more Smart Citations
“…After excluding cases with explicit unifocal involvement, involvement of both breasts, or un-reported location, 13 cases were found in the literature of DDA with multifocal involvement (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), as in our case (Table SI 1 ). Among them, 84.6% involved women, with mean age 58 years; 46.2% involved current smokers; and 46.2% featured atherosclerosis, as expected according to the review of Touloei et al (3) The thigh was the most common location, observed in 61.5% of cases.…”
Section: Multifocal Diffuse Dermal Angiomatosis: a Reflection Of High Cardiovascular Riskmentioning
confidence: 85%
“…According to the literature data, topical corticosteroids did not show to be an effective option for the treatment of DDA, explaining why we did not prescribe them despite the fact that the abdominal lesions had previously developed favourably with topical corticosteroids. The efficacy of revascularization of the involved area ( 1 , 3 , 4 , 7 , 10 , 14 ) has been reported and seems to be the most efficient treatment with extremities involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions tend to persist and progressively enlarge. [5][6][7][8] While the extremities are the most commonly reported location, there have been several reported cases of DDA of the breast (DDAB), indicating that DDAB is likely more prevalent than previously thought. 5,[9][10][11][12][13] Herein, we report a case of bilateral DDAB and review the management strategies utilized for this disease to date.…”
mentioning
confidence: 99%
“…В клинической практике известны различные поражения, обусловленные клебсиеллами. Так, при ангиоматозе кожи со вторичными кишечными изъязвлениями у 63-летней пациентки была обнаружена Klebsiella pneumoniae [12]. Данный возбудитель нередко обладает резистентностью ко многим лекарственным препаратам (РМЛП).…”
unclassified